Implementation of criminal law policy of Ukraine under martial law: a study of negative trends - Pysmenskyy Ye. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The objective of the article is to identify and provide a scholarly review of the main negative trends in the implementation of Ukraine’s criminal law policy under martial law (since the beginning of the full-scale invasion of Ukraine by Russian troops). Methodology. The research methodology used is aimed at identifying the main negative trends in the implementation of Ukraine’s criminal law policy under martial law. It is carried out on the basis of academic monitoring of the process of law enforcement in the field of criminal justice and the generalization of available research data on this issue. The study used the general methods of scientific cognition: analysis and synthesis, induction and deduction, abstraction, and generalization.Results. The following negative features are identified that are inherent in the process of implementing Ukraine’s criminal law policy in the context of a high-intensity war: erroneous and/or unequal application of criminal law norms that are flawed; inability to interpret the Criminal Code of Ukraine using all the appropriate methods; inability (unwillingness) to establish the correlation between the literal legal text and the true meaning of legal norms; attempts to use criminal law to play along with the prevailing moods in society (which are characterized by repressiveness given the conditions of an aggressive war); focusing on formal indicators in combating crime with concentration of efforts on simple cases. Originality. As a result of the study, new scholarly knowledge has been gained about the main negative characteristics of the implementation of criminal law policy in Ukraine under martial law. Practical significance. The conclusions and proposals formulated in the article can be used in research as a basis for empirical study of law enforcement as well as in lawmaking to improve criminal legislation in Ukraine.